Bronze Age Krater from Atskuri - Vakhtang Licheli (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
In 2007 archaeological excavations were carried out on the 1st century BC settlement and Middle Bronze Age burials of the Atskuri archaeological site. The most important materials were found in the Bronze Age burial on the left bank of the river Mtkvari, to the east of the classical and hellenistic period settlement. I would like to draw particular attention to the Krater, because it does not have an analogue in Caucasian archaeology. According to the items of the complex, the Krater is dated the XVII-XVI centuries BC. If we analyse materials from the Atskuri burial and other burials of the same period from the village of Ota, it is clear that after the "Brilliant culture of Trialeti" there are a few, somewhat different cultural elements, which preserve ancient traditions. In addition, in this group of traditional items there appear new cultural elements which characterise all of this complex as a new micro-culture with a diverse characteristics and rich inventory. P.S. The references can be seen after the Georgian version of the article.